The Influence of Starfall Website toward Students Reading Comprehansion in Narrative Text - M. Fikri Nugraha Kholid; Eril Syalsabila; Dewi Kurniawati (Al-Insan: Islamic and Humanities Perspectives Journal, 2025)
This research aimed to investigate the effect of the Starfall website on students’ reading comprehension of narrative texts. The study was motivated by the low reading performance of ninth-grade students at elementary school, especially in understanding complex and lengthy passages. Starfall, as a digital learning platform, was implemented to provide interactive and engaging reading input for the students. The research employed a quasi-experimental design with pre-test and post-test procedures involving an experimental group that used Starfall and a control group that received conventional instruction. The sample was selected through cluster random sampling, and the instrument used was a multiple-choice test based on Brown’s theory, including items on main idea, inference, detail, and vocabulary. The research results showed a significant improvement in the experimental group compared to the control group. Therefore, it can be concluded that the Starfall website had a positive influence on students’ reading comprehension in narrative texts and may serve as an effective alternative learning resource.